Pengaruh Variasi Lama Waktu Kontak Dan Diameter Media Karang Jahe (Acropora Sp.) Terhadap Penurunan Kadar Logam Chromium (Cr) Limbah Cair Batik Home IndustryKota Pekalongan - Maulana Syarif Hidayat (Jurnal Kesehatan Masyarakat (Undip), 2017)
Batik industry is one of the industries that produce wastewater with heavy metal pollutant parameters Chromium (Cr). Chromium (Cr) is carcinogenic and toxic in the water. Accumulation of heavy metals in environment will cause pollution and damage to ecosystem. One of the ways that can be done to reduce levels of Cr in wastewater is adsorption method using ginger coral (Acropora sp.). The purpose of this study was to determine the effect of variations in contact time (30, 60, 90, and 120 min) and the medium diameter (2,8-4,75 mm, 1,18-2,36 mm, and 0,25-1 mm) coral ginger to decreased levels of Cr in wastewater Batik home industry. This type of research is the design of experimental pretest-posttest control group design. The treatment uses a batch system. Samples of water used is partly wastewater Batik home industry. Cr inspection method was using a tool Atomic Absorption Specthrofotometer (AAS). Decreased levels of Cr were highest in medium diamater of 0,25-1 mm with a contact time of 120 minutes, amounting to 32,74 %. Two Way Anova test results obtained significance value (p-value) = 0,993 (p>0,05). The conclusion from this study is the lack of a significant interaction effect between the size of the diameter of the media used and the contact time to decrease the levels of Cr in the liquid waste of batik.